Son of a witch : a novel - Maguire, Gregory (Maguire, Gregory. Wicked years, 2005)
The sequel to Wicked returns to the land of Oz to tell the story of Liir, an adolescent boy last seen hiding in the shadows of the castle after Dorothy killed Elphaba, the Wicked Witch of the West. Bruised, comatose, and left for dead in a gully, Liir is shattered in spirit as well as in form. He is tended at the Cloister of Saint Glinda by the silent novice called Candle, who wills him back to life with her musical gifts. What dark force left Liir in this condition? Is he really Elphaba's son? He has her broom and her cape, but what of her powers? Can he find his supposed half-sister, Nor, last seen in the forbidding prison, Southstairs? Can he fulfill the last wishes of a dying princess? In an Oz that, since the Wizard's departure, is under new and dangerous management, can Liir keep his head down long enough to grow up?